Dissent with modification : human origins, palaeolithic archaeology and evolutionary anthropology in Britain 1859-1901 - McNabb, John (Archaeopress, 2012)
The author's original aim in writing this work was to chronicle the story of a very specific debate in human evolutionary studies that took place between the late 1880s and the 1930s - the 'eolith' debate that had to do with small, natural stones whose shape and edges suggested to our earliest ancestors their use as tools. These were the most primitive of tools, thought to date to the very beginning of human cultural evolution, and therefore suited to our very earliest ancestors. The more the author researched this topic the more he realised that its explanation was rooted in a number of research questions which today are considered separate subjects, and, gradually, a book that was to be about a forgotten Palaeolithic debate became a book that was just as much about 'Morlocks', stone tools, racial difference, and the Anthropological Society of London.